EFEKTIVITAS PENYELESAIAN KREDIT BERMASALAH MELALUI PARATE EKSEKUSI OBJEK JAMINAN FIDUSIA PADA LEMBAGA PERBANKAN - Izaac Lucas Dominggus Lawalata (AkMen JURNAL ILMIAH, 2017)
This study aims to provide an effective legal certainty for banking institute in the parate execution through in public auction that is set up according to Article 29 clause (1) point 2 of Act. No. 42 in 1999 concerning Fiduciary Law. But in reality, majority of banking institutions (Eastern of Indonesia) extend credit fiduciary object actually to perform parate executions without publicauctionconducted on services by State Property Office and Auction (called : KPKNL). In this paper, the authors also describe some logical reason of banking institute carried parate executions without through by KPKNL services, specifically : the first reason is technical (procedural) and the second is the non - tehnical. Parties bank institutions do it because their position as a creditor with a business-oriented principles. The author discuss about mechanisms and effectiveness of credit when non - performing loans resolution so the author enable to take conclusion as result of these studies.